2010
DOI: 10.1073/pnas.1010386107
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A impairs the double-strand break repair machinery in the germline and causes chromosome abnormalities

Abstract: Bisphenol A (BPA) is a highly prevalent constituent of plastics that has been associated with diabetes, cardiovascular disease, and an increased risk of miscarriages in humans. In mice, BPA exposure disrupts the process of meiosis; however, analysis of the affected molecular pathways is lagging and has been particularly challenging. Here we show that exposure of the nematode Caenorhabditis elegans to BPA, at internal concentrations consistent with mammalian models, causes increased sterility and embryonic leth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
126
2
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 156 publications
(147 citation statements)
references
References 56 publications
17
126
2
2
Order By: Relevance
“…They showed that the set of genes that is downregulated with the BPA/high-sugar diet displays a substantial increase in the number of genes highly expressed in testis ( Figure 4B and Table S2; P = 1.05e-13, Fisher's exact test). These results are in agreement with the observation that BPA impairs germline tissues (Allard and Colaiacovo 2010;Lawson et al 2011;Hunt et al 2012) and suggest that excess sugar might contribute to these toxic effects.…”
Section: Resultssupporting
confidence: 82%
See 4 more Smart Citations
“…They showed that the set of genes that is downregulated with the BPA/high-sugar diet displays a substantial increase in the number of genes highly expressed in testis ( Figure 4B and Table S2; P = 1.05e-13, Fisher's exact test). These results are in agreement with the observation that BPA impairs germline tissues (Allard and Colaiacovo 2010;Lawson et al 2011;Hunt et al 2012) and suggest that excess sugar might contribute to these toxic effects.…”
Section: Resultssupporting
confidence: 82%
“…The effects of BPA exposure on the impairment of chromosome synapsis and double-strand DNA break repair have previously been observed during Caenorhabditis elegans oogenesis (Allard and Colaiacovo 2010), and similar observations were noted in rhesus monkey females (Hunt et al 2012). Hunt et al (2012) further observed abnormal centromere associations, although the mechanisms have remained unclear.…”
Section: Widespread Consequences Of Disrupting the Ribosomal Machinerysupporting
confidence: 56%
See 3 more Smart Citations